Antioxidant and antimicrobial activity of the extracts from different parts of Etlingera sayapensis (Zingiberaceae) - Mahdavi, Behnam; Wan Yaacob Wan Ahmad,; Laily Din, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The rhizomes, stems and leaves of Etlingera sayapensis were extracted with ethyl acetate, acetone, ethanol and methanol to give 12 extracts. The total phenolic content (TPC) of the extracts was measured in this study, together with their antioxidant activity. Assays used were radical scavenging activity (RSA), β-carotene bleaching (BCB), ferrous ion chelating (FIC) and ferric reducing antioxidant power (FRAP). Among the assays, the leaf methanolic extract showed the highest activity with 35.67 mg GAE/g (mg of gallic acid per gram of extract) for TPC, IC50 of 53.43 μg/mL for RSA, 83.24% for BCB, IC50 of 242.43 μg/mL for FIC (second highest) and 19.53 mg TrE/g (mg of Trolox per gram of extract) for FRAP. The measured BCB values for the four leaf extracts were higher than those of the positive controls of butylated hydroxytoluene (BHT), gallic acid (GA) and ascorbic acid (AscA) and slightly lower than that of α-tocopherol (Toc). The antimicrobial activity of the extracts was also measured using disc-diffusion (DD) and minimum inhibition concentration (MIC) assays. Among the extracts, only ethanolic and methanolic extracts showed specific bacterial inhibition against Bacillus subtilis. Only stem methanolic extract exhibited specific fungal inhibition against Candida parapsilosis. The highest activity was shown by this with 9.9 mm and 1.04 mg/mL for DD and MIC assays respectively.